The Effectiveness of Using Prezi Learning Media on the Learning Outcomes of Eighth-Grade Students in Informatics at MTs Negeri 2 Sidrap - Hajar Istiqoamah; Abd Kahar; Muhammad Takdir; Madaling Madaling (Universitas Muhammadiyah Enrekang, 2025)
This study aims to determine the effectiveness of using Prezi learning media on the learning outcomes of eighth-grade students in the Informatics subject at MTs Negeri 2 Sidrap. The background of this study is based on the importance of using interactive and engaging learning media to enhance students' understanding in technology-based learning. The method used is a quantitative approach with a pre-experimental design of the one-group pretest-posttest type. The sample in this study consists of 33 students from class VIII.A. Data collection techniques include tests and questionnaires. The results of the study show an increase in the average score from a pretest of 68.93 to a posttest of 88.90. Additionally, the questionnaire results indicate that the majority of students gave positive responses to the use of Prezi media, both in terms of learning mastery and time efficiency in the learning process. Therefore, it can be concluded that the use of Prezi learning media is effective in improving student learning outcomes in the Informatics subject.